A Comparison of Reclamation/Closure Plans of Three Mine Sites in the NWT - Young, Annie (2020)
Mining in the Northwest Territories is a profitable industry that provides employment opportunity for local communities and resources required for everyday use, however mining is a source of environmental stress on the surrounding ecosystem. Issues arise regarding abandonment of mine sites, as well as improper remediation. A series of steps have been taken to reduce the socio-economic and environmental impact that mining operations have. Environmental impact assessments have been developed and incorporated into the planning process, which work to maintain corporate social responsibility of the companies performing mining activities. Closure plans are a critical component of environmental assessments, which are vastly detailed documents that describe the specifics of final landform and surface rehabilitation, post-closure monitoring protocols and reflect the context of each project. This study uses document/thematic analysis to extract a set of evaluation criteria for mine closure from a Mackenzie Valley reference document commonly used in the Northwest Territories. Furthermore, an analysis of three closure and reclamation reports were evaluated for post closure monitoring activities at the site – wide and individual project scale in comparison to the reference document. The three closure reports were discussed in terms of content, specifically how in depth they referred to their monitoring programs at each of the two scales, as well as in terms of the readability and structure of the plans. Research concluded that to maintain clarity, the structural format of the closure plans and inclusion of a variety of tables and figures was useful for effective communication of information. The results of this review indicate that of the three closure and reclamation reports, Giant Mine presented the most extensive list of monitoring programs per post closure monitoring action.